The role of surfactant protein-A in sinusitis. Issue 1 (February 2019) - Chang, Eugene H.
Abstract : Purpose of review: Surfactant protein-A (SP-A) is a collectin protein expressed in airway epithelia that is critical in the modulation of both innate and adaptive immunity against inhaled pathogens. In this review, we highlight associations of altered SP-A function in asthma and chronic rhinosinusitis, and its potential role as a targeted therapy for sinusitis. Recent findings: SP-A has been shown to bind and opsonize inhaled pathogens, thereby clearing bacteria through phagocytosis. We have recently identified that SP-A levels are increased in response to Pseudomonas aeruginosa, a common bacterial pathogen in chronic rhinosinusitis. Moreover, SP-A has also been shown to modulate epithelial inflammatory mediators and play a role in eosinophil-mediated airway disease. The development of a transgenic murine model expressing human genetic variants of SP-A2 have suggested that the human surfactant protein-A2 223K variant significantly increases eosinophil degranulation, suggesting a genotype-phenotype correlation in human airway disease. Summary: SP-A is important in both the innate and adaptive host defense mechanisms in the upper and lower airways. Although research in this field in sinusitis is nascent, initial work suggests that aberrant SP-A regulation may be one etiologic factor in the development of bacterial and eosinophilic-associated sinusitis.